Aplikasi Get Rent Car - Herried Jonatan Andries; Adi Wibowo; Henry Palit (Jurnal Infra, 2017)
Semarang is a fast growing city, many people are coming from various regions to enjoy both the tourism and the culinary in Semarang. Not infrequently people spend a few days to get around enjoying it all and most of the people are confused or do not know what to do with them around Semarang. They do not know where to rent a car.From these problems, it takes an application to make it easier for tourists and people of Semarang to do car rentals that will be used to get around Semarang. Get Rent Car Application in it also features Google Calendar which can automatically add events in your android calendar to be able to provide a reminder to the user. In this application also the user can negotiate rental rates.Based on the results of the questionnaire, on the tenants 20% of respondents assessed the application view is enough, 60% of respondents rate good, and 20% of respondents very good. For rating review & rating assessment, 20% of respondents are enough, 40% of respondents rate good, and 40% of respondents are very good. For the assessment of negotiation features, 20% of respondents considered enough, 40% of respondents rated good, and 40% of respondents were very good. For the assessment of Google Calendar feature 40% of respondents rate enough, 40% of respondents rate good, and 20% of respondents very good. For ease of appraisal appraisal 40% of respondents rate good and 60% of respondents are very good. For assessment of conformity with the needs of 20% of respondents considered enough, 60% of respondents rate good, and 20% of respondents very good. For the overall app assessment 60% of respondents rated good and 40% of respondents very well.